MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE SILABA UNTUK ANAK BERKESULITAN BELAJAR KELAS 2 SD NEGERI 09 KOTO LUAR PADANG - Rahmat Hidayat (Universitas Negeri Padang, 2014)
Abstract: This research is in the background by the background issues that appear in the field, the kid learning difficulties in primary school class II X 09 Koto Affairs field who have difficulty in reading the word. This is evident from the beginning of the child's ability to read words children have difficulty on tests that researchers provide. children may not be able to answer all the test correctly. This study uses a Single Subject Research approach, the AB design and data analysis techniques using visual analysis chart. The results of this study indicate that the method is able to improve the reading skills silaba beginning of learning difficulties for children 2nd grade at SDN 09 Padang koto outside.